THE EFFECT OF AUDITOR’S COMPETENCE AND INDEPENDENCE ON INFORMATION SYSTEM AUDIT QUALITY - Santy Setiawan; Yenni Carolina; Aura Kristiani (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
Users of financial statements always rely on the results of audits conducted by competent andindependent auditors because the audits are carried out through quality processes and efforts. Competent and independent auditors are needed to obtain quality audit results. Because most modern information systems use information technology, the information technology audits become an important component in all external and internal audits. This study aims to examine the effect of auditor’s competence and auditor’s independence on the information systems audit quality. The research sample used in this study is external auditors working in public accounting firms in West Java. The statistical test instrument used is a multiple regression test. The results show that the auditor's competence has an effect on information systems audit quality, while the auditor’s independence has no effect on information systems audit quality.